Confessions of an Economic Hit Man - Perkins, John 1945- (London Ebury Press, 2006)
As an EHM in the '60s and '70s, covertly recruited by the US National Security Agency, John Perkins helped further American imperial interests in countries such as Ecuador, Panama, Indonesia and Saudi Arabia. He tried to write this book four times but was threatened or bribed each time to halt. The events of 9/11 forced him to reveal the truth.
Include Notes and Index
Keywords: Perkins, John, -- 1945- -- United States. -- National Security Agency -- Biography